Nurse Overestimation of Patients' Health Literacy - Dickens, Carolyn (Taylor & Francis, 2013)
Patient education and effective communication are core elements of the nursing profession; therefore, awareness of a patient's health literacy is integral to patient care, safety, education, and counseling. Several past studies have suggested that health care providers overestimate their patient's health literacy. In this study, the authors compare inpatient nurses' estimate of their patient's health literacy to the patient's health literacy using Newest Vital Sign as the health literacy measurement. A total of 65 patients and 30 nurses were enrolled in this trial. The results demonstrate that nurses incorrectly identify patients with low health literacy. In addition, overestimates outnumber underestimates 6 to 1. The results reinforce previous evidence that health care providers overestimate a patient's health literacy. The overestimation of a patient's health literacy by nursing personnel may contribute to the widespread problem of poor health outcomes and hospital readmission rates.